Adsorption and Recovery of Methylene Blue from Aqueous Solution by NaOH-Treated of Prina - Hamdi Karaoglu, M.; Ugurlu, Mehmet (Asian Journal of Chemistry, 2011)
In the present work, we have investigated the sorption efficiency of base activated prina towards methylene blue removal from their respective aqueous solutions. Base activated prina material was prepared by treatment of olive stones and aqueous solution at room temperature. The resulting material has been thoroughly characterized by FTIR. The sorption study of 0.1 M NaOH base activated prina at the solid-liquid interface was investigated using adsorbent dosage, initial pH, initial dye concentration, temperature and ionic strength. The application of the Langmuir and Freundlich models showed a better fitting of experimental data to the first model. Base activated prina exhibited the highest methylene blue uptake of 12.90 mg/g at natural pH. The methylene blue adsorbed could be desorbed by ultrapure water, ethyl alcohol and hydrochloric acid. In the kinetic of the adsorbent process, the adsorption data followed the second-order kinetic model better than first order kinetic model and particle diffusion models. In addition, the diffusion coefficient values was found in the range from 0.62 × 10-7-31.79 × 10-7 cm2/s. Isotherms have also been used to obtain the thermodynamic parameters such as free energy, enthalpy and entropy of adsorption. The positive value of the enthalpy change (68.122 kJ mol-1) indicated that the adsorption is endothermic process. The results indicate that base activated prina could be fruitfully employed as effective biomaterial and as low-cost sorbents for the removal of methylene blue from effluents.